The relationship of parental characteristics with adolescents' knowledge and attitudes regarding early marriage - Wardani, Diadjeng Setya; Nurazizah, Devita Alifia; Jannah, Miftahul; Putri, Rismaina (Science Midwifery, 2024)
East Java is the province with the highest rate of child marriage, which is 10.44% higher than the national average. Early marriages carried out by minors are also inseparable from the role of parents. In this study, the characteristics of parents that will be studied are education, employment status, income and history of early marriage. To determine the relationship between parental characteristics and teenagers' attitudes and knowledge about early marriage. This research uses an analytical survey method with a cross-sectional study approach. This research was attended by 80 students and pupils who met the inclusion criteria. Data collection was carried out using a questionnaire. Bivariate analysis used the Chi-square test with a significance value of 5%. There is no relationship between parental characteristics and student knowledge. Apart from that, there is no relationship between employment status and parental income and student attitudes. However, there is a significant relationship between recent education (p value 0.048) and parents' history of early marriage (p value 0.006) with students' attitudes. Recent education and history of early marriage of parents have a significant relationship with students' attitudes at State Islamic Boarding School Al-Maarif 03 Singosari, Malang.